Kebijakan Publik dan Kinerja Birokrasi Pendidikan Dalam Kompleksitas Perkembangan: - Chaira Saidah Yusrie; Siti Aminah; Iim Wasliman; R Supyan Sauri (Jurnal Dirosah Islamiyah, 2021)
In essence, development is a systematic and planned effort by each or all components of the nation to change a situation into a better condition by utilizing various available resources optimally, efficiently, effectively and accountably, with the ultimate goal of improving the quality of human life and society in a sustainable manner. Planning is a process that describes the goals of the organization and determines the strategies that will be used to achieve organizational goals. Planning is an important process of all management functions because without planning, the function of organizing, controlling and directing will not work. The research that the author uses is a type of literature review research or often called library research, Library Research which is research that is focused on collecting a series of quotations from various books or articles and laws / regulations related to the object of study. There are several challenges to realizing sustainable development in a concrete manner in various fields and regions, namely: There is still a need for commonalities and widespread understanding by various stakeholders about the importance of sustainable development in all aspects of life; Development of data and measures of sustainable development and their reflection into concrete activities, both in the environmental, economic and social dimensions reflected in sustainable behavior; The importance of developing and encouraging the implementation of environmentally friendly activities reflected in the efficient use of resources and reducing waste, strengthening pollution monitoring including facilitation and support for its expansion; Development of governance that encourages the use of clean resources and technology, including measures to control pollution and law enforcement efforts accompanied by capacity building of institutions and human resources as a whole. There are five national development priorities in the 2020 RKP: National development and poverty alleviation; Infrastructure and equitable distribution of areas; Added value in the real sector and industrialization as well as expanding job opportunities; Food, water, energy and environmental security; and Defense stability and security.